A Contemplation about the Importance of Prosthetic Defect Classification Systems in Contemporary Dentistry - Z. Zdráhal; J. Krňoulová; R. Slezák (Czech Dental Chamber, 2012)
Introduction: The aim of the dental care is ensuring the biological and social functions of dentition throughout all the life of an individual. Planning prosthetic reconstruction is based on the analysis of all available data (e. g., history, clinical findings, imaging techniques, etc.). There are several classifications of the dental arch defects which determine the type of the defect. Some deal with the placement of the remainig teeth and gaps, others with shortened dental arches and gaps, presence of so-caled supporting zones or teeth having regard to the transfer of the chewing pressure. Objectives: The authors describe the seven best-known classification systems according to Voldřich, Kennedy, Wild, Eichner, Witter, Körber, and Tvrdoň. They describe the distribution of prosthetic teeth defects to certain groups or classes in terms of conventional and implantology prosthetic dentistry. They present the most common treatment options prosthetic defects - frontal gap, unilaterally or bilaterally shortened dental arch, loss of half of the dental arch, toothless jaw, the first two prosthetic defects are divided into subgroups, differing number of teeth lost. They recapitulate the current possibilities of reconstruction of the above defects using implantology and conventional prosthetic dentistry. The authors discuss this issue in the context of current possibilities of prosthetic treatment modes and try to answer the question, if this knowledge still remains useful and reveals practical use.